2015
DOI: 10.1155/2015/694068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Dimple Bionic Nonsmooth Surface on Tire Antihydroplaning

Abstract: Inspired by the idea that bionic nonsmooth surfaces (BNSS) reduce fluid adhesion and resistance, the effect of dimple bionic nonsmooth structure arranged in tire circumferential grooves surface on antihydroplaning performance was investigated by using Computational Fluid Dynamics (CFD). The physical model of the object (model of dimple bionic nonsmooth surface distribution, hydroplaning model) and SST k − ω turbulence model are established for numerical analysis of tire hydroplaning. By virtue of the orthogona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Shi et al analyzed the effect of bionic serrated structures on the aerodynamic noise of a circular cylinder and point out that the aerodynamic noise can be reduced in the case of the cylinder with serrated structures [9]. In addition, bionic nonsmooth structures are applied for noise reduction in high-speed trains [10], automobile bodies [11], aircraft designs [12], and tire patterns [13], and studies have indicated good prospects for flow engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al analyzed the effect of bionic serrated structures on the aerodynamic noise of a circular cylinder and point out that the aerodynamic noise can be reduced in the case of the cylinder with serrated structures [9]. In addition, bionic nonsmooth structures are applied for noise reduction in high-speed trains [10], automobile bodies [11], aircraft designs [12], and tire patterns [13], and studies have indicated good prospects for flow engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…While the staggered patterns exhibited the greatest heat transfer performance, the lined pattern showed the second greatest performance. Zhou et al [13] studied how the dimple bionic structure inserted in the circumferential grooves' surface influenced fluid resistance by comparing the drag coefficient of dimple bionic structure with that of smooth structure. They found that the dimple bionic structure could reduce fluid resistance because the dimple bionic structure decreased the pressure drop because of driving fluid to raise the velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of bionic nonsmooth surfaces, like riblets and others, are already used in industrial flows to obtain drag reduction successfully [ 14 18 ]. Actually, the nonsmooth surfaces mainly achieve the drag reduction by decreasing the friction loss in boundary layers, which also have their potential drag reduction in torque converter.…”
Section: Introductionmentioning
confidence: 99%